Interactions between rat cortico-striatal slice cultures and neutrophil-like HL60 cells under thrombin challenge: Toward elucidation of pathological events in intracerebral hemorrhage - Daisuke Noda; Yuki Kurauchi; Akinori Hisatsune; Takahiro Seki; Hiroshi Katsuki (Elsevier, 2020)
Neutrophils constitute the major population of infiltrating leukocytes after stroke including intracerebral hemorrhage (ICH), and these cells may exhibit pro-inflammatory and anti-inflammatory phenotypes depending on the external stimuli. Here we constructed an experimental system to evaluate how the properties of neutrophils were influenced by the injured brain tissues. HL60 cells differentiated into neutrophils were added to the culture medium of neonatal rat cortico-striatal slices maintained at liquid-air interface. Thrombin was applied to the cultures to mimic the pathogenic events associated with ICH. HL60 cells responded to thrombin by increasing mRNA expression of pro-inflammatory IL-1β and anti-inflammatory IL-10 with a different time course. Co-presence of cortico-striatal slice cultures significantly enhanced IL-1β mRNA expression, whereas attenuated IL-10 mRNA expression, in HL60 cells. Toll-like receptor 4 (TLR4) agonist lipopolysaccharide synergistically enhanced IL-1β mRNA expression with thrombin, and TLR4 inhibitor TAK-242 abolished thrombin-induced IL-1β mRNA expression in the presence of slice cultures. On the other hand, thrombin-induced cell death in cortico-striatal cultures was attenuated by the presence of HL60 cells. This experimental system may provide a unique platform to elucidate complex cell-to-tissue interactions during ICH pathogenesis. Keywords: Hemorrhagic stroke, Neuroinflammation, Neutrophil polarization, Cytokine, Alarmin